A Companion to Genethics. - Burley, Justine (Blackwell companions to philosophy., 2007)
A Companion to Genethics is the first substantial study of the multifaceted dimensions of the genetic revolution and its philosophical, ethical, social and political significance.; Brings together the best and most influential writing about the ethics of genetics;.; Includes 33 newly-commissioned essays, all written by prominent figures in the field;.; Shows how there is scarcely a part of our lives left unaffected by the impact of the new genetics.